Men's perception of current and ideal body composition and the influence of media internalization on body judgements - Groves, Vicki; Ridley, Bethany J.; Cornelissen, Piers L.; Maalin, Nadia; Mohamed, Sophie; Kramer, Robin S. S.; McCarty, Kristofor; Tovée, Martin J.; Cornelissen, Katri K. (Frontiers in Psychology, 2023)
Introduction To determine men's body ideals and the factors that influence these choices, this study used a matrix of computer generated (CG) male bodies (based on an analysis of 3D scanned real bodies) which independently varied in fat and muscle content. Methods Two hundred and fifty-eight male participants completed a range of psychometric measures to index body concerns and body ideal internalization and then chose the CG body that best reflected their own current body, as well as the body that reflected their personal ideal. A subset of participants was then retested to check that these judgements were stable over time. Results While judgements of the ideal body seem to be influenced by a shared appearance ideal, the degree to which this ideal was internalized showed significant variability between participants. The effect of this internalization was reflected in the difference between the estimated current body and the ideal. Discussion Higher internalization led to a preference for higher muscle and lower fat content. This preference was most marked for fat content, although reducing adiposity also made the underlying musculature more salient. Additionally, the ideal body composition was modulated by the composition the participant believed his current body had (i.e., it seemed that a participant's ideal body was anchored by what they believed to be their current body and what change was possible from this starting point).